Modeling using baseline characteristics in a small multicenter clinical trial for Barrett’s esophagus - Shar, Albert O. (2008)
OBJECTIVE: Utilizing data obtained during a multicenter investigation, this paper illustrates how the use of covariates and careful modeling techniques can be useful in assessing whether a negative outcome from a small multicenter clinical trial could be due to imbalance in baseline characteristics. The Chemoprevention for Barrett’s Esophagus Trial (CBET) was a phase IIb, multicenter, randomized, placebo-controlled trial of celecoxib in patients with Barrett’s esophagus. The primary outcomes for the original study were the proportion of biopsy samples exhibiting dysplasia in the celecoxib and placebo groups. The secondary and tertiary outcomes included histologic change and measurements of biologically relevant markers, including COX-1 and –2 mRNA, prostanoid levels, and methylation of tumor suppressor genes p16, APC, and E-cadherin. The original study reported no significant differences in primary, secondary or tertiary outcomes. In this paper, we focus on the results of one of the secondary measures, quantitative endoscopy (QE). DESIGN: The study utilizes data from 56 patients in the CBET for whom baseline (BL) QE and one-year follow-up QE (F04) studies were performed. Of these, 29 were treated with celecoxib (200 mg twice daily for a minimum of 48 weeks) and 27 received the placebo. These patients are segmented as to the presence or absence of circumferential, tongues or islands of Barrett’s. MEASUREMENTS: The response of interest is total affected area at one year (Total F04); affected area at baseline (Total BL) is used as a covariate. RESULTS: Controlling for complexity and clinic, there is a significant treatment effect. In addition, there is significant evidence that the area of Barrett’s involvement decreased for patients in the treatment group. CONCLUSIONS: That there was a decrease for the celecoxib over the placebo group adds to the body of evidence that relates COX-2 specific inhibitors and cancer incidence.